Horatio’s drive :America’s first road trip.Disc three [CD-ROM] /Dayton Duncan, Ken Burns - Duncan, Dayton
Read by author, with Tom Hanks, Philip Bosco, Kevin Conway, Jonathan Davis, and George Plimpton